Putting susceptibility on the map to improve conservation planning, an example with terrestrial mammals. Issue 8 (9th June 2016) - Polaina, Ester; Revilla, Eloy; González‐Suárez, Manuela
Abstract: Aim: To propose a general approach to spatially synthesize known predictors of vulnerability at the species level in order to identify areas directly associated with specific conservation problems. Under this problem‐detection framework, the coincidence or divergence of main strengths and weaknesses can be used to propose tailor‐made conservation strategies. This approach is illustrated for terrestrial mammal species evaluating two of their main components of vulnerability: life‐history traits and land‐use pressure. Location: Global. Methods: We determine, at the species level, the relationships between extinction risk and two well‐known predictors of vulnerability: life‐history traits (intrinsic) and land use (extrinsic). Transferring these findings into the spatial domain, we identify the areas of the world where one of these two facets is predominant and those areas where both coincide. Results: The proposed approach allows us to recognize four types of areas: (1) double‐susceptibility areas : where both the characteristics of the species and the existing human activities pose a threat, therefore the simultaneous management of both species/habitats and human activities are needed; (2) intrinsic‐susceptibility areas : where species are naturally fragile and human presence is scarce, thus species‐specific management plans would be particularly efficient; (3) extrinsic‐susceptibility areas : where human pressure is high but species are not intrinsically vulnerable; which requires special attention to human activities; and (4) low‐susceptibility areas : where there are not remarkable threats for existing terrestrial mammals, which additionally are not particularly fragile. Main conclusions: Our approach can spatially synthesize known predictors of vulnerability identifying areas where different factors predispose species to become extinct. This method builds on conservation planning approaches by targeting actions based on known strengths and weaknesses of a given area, and offering a new implementation of comparative studies of extinction risk. This approach may be applied to different species and to particular regions, focusing on different drivers, and complemented by incorporating social and economic trade‐offs.